Salvia greggii Cherry Sage, Autumn Sage, Cherry Salvia: FPS524/FP524, 8/2007 - Gilman, Edward; Marshall, David (EDIS, 2007)
This document provides an overview of Salvia greggii, commonly known as cherry sage, autumn sage, or cherry salvia. It details the plant’s characteristics, including its height, spread, leaf arrangement, and flower colors. The document highlights its native range in North America and its adaptability to various soil types and climates, particularly USDA hardiness zones 7B through 11. It also discusses the plant’s uses in landscaping, its moderate drought tolerance, and its attractiveness to hummingbirds and butterflies. Additionally, the document covers planting guidelines, propagation methods, and pest resistance, noting that cherry sage is generally free from major pest and disease issues. Original publication date October, 1999.